2010
DOI: 10.1093/jnci/djq093
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-Specific Stem Cell Selection During Malignant Transformation

Abstract: An apparent stem cell survival advantage with regard to arsenic causes selection during malignant transformation that manifests itself as an overabundance of CSC-like cells specifically after arsenic-driven acquisition of malignant phenotype. The increased resistance to apoptosis and arsenite hyper-adaptability of WPE-stem cells suggests that arsenite transformation of RWPE-1 cells involves an increase in the number of CSC-like cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
95
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 58 publications
10
95
0
1
Order By: Relevance
“…An additional possibility is that the increased ALDH1A1 expression might be related to an increased number of cancer stem cells in the iAs transformants but not in the Cd and MNU transformants as previously reported (Tokar et al , 2010; Tokar et al , 2011). This may also explain why ALDH1A1 was differentially expressed, being upregulated in the CAsE-PE but downregulated in the CTPE and B26..…”
Section: Discussionmentioning
confidence: 77%
“…An additional possibility is that the increased ALDH1A1 expression might be related to an increased number of cancer stem cells in the iAs transformants but not in the Cd and MNU transformants as previously reported (Tokar et al , 2010; Tokar et al , 2011). This may also explain why ALDH1A1 was differentially expressed, being upregulated in the CAsE-PE but downregulated in the CTPE and B26..…”
Section: Discussionmentioning
confidence: 77%
“…3 A, B). This prompted us to investigate innate resistance to arseniteinduced cytolethality since this was a trait associated with stemness in RWPE-1 cells as previously described [22]. After short-term (ie, 48 h) arsenite exposure (Fig.…”
Section: S-ship-gfp Promoter Reporter Tracks Subsets Of Rwpe-1 Cells mentioning
confidence: 99%
“…To test this hypothesis, we used as a model the nontumorigenic human prostate cell line RWPE-1 that was derived from normal human prostate epithelium immortalized by human papillomavirus 18 [20]. RWPE-1 cells and its derivatives contain stem, intermediate, and differentiated cell types and offer valuable models for studies of adult prostate stem cells [21,22].…”
mentioning
confidence: 99%
“…Furthermore, other recent studies showed that As 3+ is able to activate a signaling cascade from JNK and Stat3 to Akt-mediated EZH2 phosphorylation, which may be linked to the epigenetic reprogramming of the genome and the malignant transformation of cells [5]. Finally, As 3+ had been shown to be capable of converting normal stem cells into cancer stem cells (CSCs) in several experimental settings [6, 7]. …”
Section: Introductionmentioning
confidence: 99%